Transgression of Desire in Erotica Based on the Psychoanalysis of Jacque Lacan and George Bataille - Tuwio, Namuri Migo; Djohan, Djohan; Harsanto, Prayanto Widyo (IJCAS (International Journal of Creative and Arts Studies), 2024)
This study aims to develop a new discourse of eroticism based on the experience of sexual fantasy as an effort to find "self-meaning" through the practice of creating works of art. So far, the concept of eroticism is still widely misunderstood as a taboo that is narrowly interpreted as a reflection of sexuality through works of art, thus creating a negative impression and contradicting the values that develop in society. Eroticism contains a great essence as a concept that can bring the paradigm of sexuality to a different level. The psychoanalytic perspective, the theory of the Four Discourses, the Graph of Desire, and George Bataille's Transgression theory support synthesizing the new concept of eroticism as a manifestation of desire in fantasy. This is related to efforts to strengthen self-conceptualization of the sensation of fear of cruelty due to a strong association with transgressive behavior and longing for the fulfillment of a sense of loss. As a tool in realizing the above research, the Practice-led Research (PLR) Method is used, namely research driven by the practice of creating art, which is a way to systematically reflect and evaluate in creating works. Thus, creating works is carried out simultaneously in stages and back and forth. The results of this study are in the form of installation art, and illustration-augmented reality as a medium for manifesting the sensation of erotic experience (sexual fantasy). Based on the study conducted, three critical things were concluded as research findings: first, erotica can be used as a medium to reflect erotic experiences; second, the method of creating "Erotika Fantasiana" involves the experience of sexual fantasy as the main material object; the third, sexual fantasy that is full of the concept of transgression, experiencing pain, and efforts to restore "loss" of self-esteem through the fulfillment of the object of desire is an important element in the concept of "Erotika Fantasiana". Transgresi Hasrat dalam Erotika Berdasarkan Psikoanalisis Jacque Lacan dan George Bataille Abstrak Penelitian ini bertujuan untuk mengembangkan wacana baru erotisme berdasarkan pengalaman fantasi seksual sebagai upaya menemukan “makna diri” melalui praktik penciptaan karya seni. Selama ini konsep erotisme masih banyak disalahpahami sebagai hal tabu yang secara sempit dimaknai sebagai refleksi seksualitas melalui karya seni, sehingga menimbulkan kesan negatif dan seolah bertentangan dengan nilai-nilai yang berkembang di masyarakat. Padahal erotisme memuat esensi besar sebagai konsep yang mampu membawa paradigma seksualitas di tataran yang berbeda. Perspektif psikoanalisis, teori Empat Wacana, Graph of Desire, serta teori Transgresi George Bataille digunakan untuk mendukung pembentukan sintesis atas konsep baru erotisme sebagai perwujudan hasrat dalam fantasi. Hal ini terkait dengan upaya penguatan akan perseptualisasi diri pada sensasi ketakutan terhadap kekejaman sebagai akibat dari asosiasi yang kuat dengan perilaku transgresif serta kerinduan terhadap pemenuhan rasa kehilangan. Sebagai alat dalam mewujudkan penelitian di atas, digunakan metode Practice Led Research (PLR) yakni penelitian yang didorong oleh praktik penciptaan seni, merupakan cara untuk melakukan representasi sensasi pengalaman sublum dan mengevaluasinya secara sistematis sebagai serangkaian proses penciptaan karya seni. Dengan demikian, proses penciptaan karya dilakukan secara bertahap dan ulang alik secara bersamaan. Hasil penelitian ini berupa karya seni instalasi, lenticular, videografi, serta ilustrasi-augmented reality sebagai medium representasi sensasi pengalaman erotisme (fantasi seksual). Berdasarkan studi yang dilakukan, disimpulkan tiga hal penting sebagai temuan penelitian: pertama, erotika dapat digunakan sebagai medium untuk merepresentasikan sensasi pengalaman erotis; kedua, metode penciptaan Erotika Fantasiana melibatkan pengalaman fantasi seksual sebagai objek material utama; ketiga, fantasi seksual yang sarat akan konsep transgresi, penghayatan rasa sakit, dan upaya pemulihan loss harga diri melalui pemenuhan objek hasrat menjadi unsur penting dalam konsep Erotika Fantasiana.